Oxygen. - Leah Solla (Issues in Science and Technology Librarianship)
This article reviews the theatre production Oxygen at the San Diego Repertory Theatre in April 2001. It is a collaboration between two well-honored academic research chemists, Carl Djerassi, professor of chemistry at Stanford University and Roald Hoffmann, Frank Rhodes Professor of Humane Letters at Cornell University. Djerassi is known for the first synthesis of a steroid contraceptive and Hoffmann received the Nobel Prize in Chemistry in 1981.